Uji Eksperimental Sambungan Pelat Baja Perantara dengan Sekrup Kunci pada Hubungan Balok-Kolom Kayu Meranti Merah - Agustina, Theresia; Tjondro, Johannes Adhijoso; Setiawan, David (Siklus : Jurnal Teknik Sipil, 2024)
Research was conducted by testing the connection of solid red meranti wood beam and column using intermediate steel plate with lag screw as fasteners. There were 3 connection samples tested under monotonic load. Material properties of red meranti wood, testing of steel tensile strength, and testing of lag screw bending yield momen has been done to design connection. The behaviour studied in this research is moment capacity, rotation of connection, and ductility of connection. The test results show that initial stiffness of connections B-1, B-2, and B-3 resulting in ranges 10,17 N/mm – 19,05 N/mm. The connections experience plastic hinge with the plastic hinge load is 1617,37 N. The plastic hinges occur in the lag screws tightening area characterized by yielding in that area. The connection ductility resulting in ranges 4,0097 – 4,7642.